Walking on streets-in-the-sky: structures for democratic cities. Issue 1 (1st January 2019) - Cunha Borges, João; Marat-Mendes, Teresa
ABSTRACT: Streets-in-the-sky were conceptualized by architects Alison and Peter Smithson as collective space, an articulation between individual and civitas. This essay argues that streets-in-the-sky are a particularly democratic type of urban element, which also has many positive sustainability potentials. The first use of this concept was in the Smithson's unbuilt Golden Lane estate (1952), which became a hallmark in post-WW2 debates over urban structure, domesticity, and social housing. Park Hill, the first streets-in-the-sky estate by Jack Lynn and Ivor Smith, was a success in the 1960s. The Smithsons continued to explore the idea in several urban projects, only to put it to built form in Robin Hood Gardens (1968–1972). These estates have adapted streets-in-the-sky and afterward evolved to very different states of maturity. While Park Hill is a refurbished Grade II listed building, Robin Hood Gardens is awaiting full demolition. Streets-in-the-sky were generally abandoned in more recent housing schemes, but the situation of these estates suggests that no consensus exists as to their urban value. Here, we analyze streets-in-the-sky at the time of their emergence as a concept. To assess their cultural, morphological, social, and political implications, we explore their development in built and unbuilt housing schemes, using the abovementioned case-studies to point out how streets-in-the-sky evolved, including their possible role in important urban debates of the present. Since many social housing estates employing streets-in-the-sky have been and continue to be demolished in redevelopment projects, we aim to understand what losses—aesthetic, functional, and environmental—may be implied in the decimation of this element of urban form.